Efficient traceless modification of the P1 bacteriophage genome through homologous recombination with enrichment in double recombinants: A new perspective on the functional annotation of uncharacterized phage genes - Bednarek, Agnieszka; Giermasińska-Buczek, Katarzyna; Łobocka, Małgorzata (Frontiers in Microbiology, 2023)
The advent of high-throughput omic technologies caused unprecedented progress in the research on bacteriophages, the most abundant and still the least explored entities on earth. Despite the growing number of phage genomes sequenced and the rejuvenation of interest in phage therapy, the progress in the functional analysis of phage genes is slow. Simple and efficient techniques of phage genome targeted mutagenesis that would allow not only to knock out particular genes without polar effects but also to study the effect of their changed products on phage functions are lacking. Even in the case of model phages, the functions of about half of their genes are unknown. P1 is an enterobacterial temperate myophage of clinical significance, which lysogenizes cells as a plasmid. It has a long history of studies, serves as a model in basic research, a gene transfer vector and a source of genetic tools. Its gene products have structural homologs in several other phages. In this perspective article, we describe a simple, and efficient procedure of trace-less P1 genome modification that could also serve to acquire targeted mutations in the genomes of certain other temperate phages and speed out functional annotations of phage genes.